Odpowiedzi

Najlepsza Odpowiedź!
2010-01-13T18:06:04+01:00
A)3x+a=2x+1
a=2x+1-3x
a=-x+1

b)-x+a+b=2a-3b-2x
-x+2x=2a-3b-a-b
x= a -4b

c)2(x+m)=m-4x+5
2x+2m=m-4x+5
2m-m=-4x+5-2x
m=-6x+5

d)x-3(n+2x)=4n+2x
x-3n-6x=4n+2x
x-6x-2x=4n+3n
-7x=7n /:(-7)
x=-n

11 5 11
2010-01-13T18:08:57+01:00
A)
3x+a=2x+1
a=2x +1 -3x
a= 1-x


b)
-x+a+b=2a-3b-2x
-x +2x = 2a -3b -a -b
x= a -4b


c)
2(x+m)=m-4x+5
2x +2m = m -4x +5
2m -m = -4x +5 -2x
m = 5 -6x


d)
x-3(n+2x)=4n+2x
x -3n -6x = 4n +2x
x -6x -2x = 4n +3n
-7x = 7n
x = -n
5 4 5